In Silico Study of Five SARS CoV-2 Target Proteins on Known Drugs: In silico study of five SARS CoV-2 target proteins - Jamshidi, Zahra; Akaberi, Maryam; Hadizadeh, Farzin (Iranian Journal of Pharmaceutical Sciences, 2021)
COVID-19 is an infectious disease that started at the end of 2019 in China then became pandemic worldwide. A number of crystal structures of coronavirus proteins are available in the Protein Data Bank. In this paper, we reported results from the virtual screening of databases including 2701 FDA approved drugs against five known coronavirus protein targets. Our results showed a wide range of scores for different drugs of which some were predicted to be active against one or some of the proteins. Among all of the compounds with higher scores, tannic acid and cobicistat showed to be active against four and two of the studied proteins respectively. Tannic acid which was reported to be an antiviral and potent inhibitor of hepatitis C virus activity and cobicistat with anti- HIV activity might be useful for the cure of COVID-19. According to the results, we suggest more studies on these valuable potential drugs.